RICH DAD'S INCREASE YOUR FINANCIAL IQ : Mengurus Wang Secara Bijak - KIYOSAKI, Robert T., 1947- (Kiyosaki, Robert T., 1947- Rich dad series., 2014)
Emphasizes the importance of financial intelligence to good money management and describes how to improve financial information and increase, protect, budget, and leverage money.